A Simple Method for the Determination of the Partitioning of Nitroxide Probes in Microheterogeneous Media - Torres-Gaona, M; Aliaga-Vidal, C; Aliaga-Vidal, C (2012)
The use of the ESR g-factor of spin labels for the easy and clean assessment of their partitioning in microheterogeneous media is described. The method constitutes a valuable alternative in those cases where the classical Benesi-Hildebrand treatment, based on UV-visible measurements, is difficult or not feasible. Copyright © 2012 John Wiley & Sons, Ltd.